Characterisation of Bacteriophage vB_SmaM_Ps15 Infective to Stenotrophomonas maltophilia Clinical Ocular Isolates - Dragica Damnjanović; Xabier Vázquez-Campos; Lisa Elliott; Mark Willcox; Wallace J. Bridge (Viruses, 2022)
Recent acknowledgment that multidrug resistant Stenotrophomonas maltophilia strains can cause severe infections has led to increasing global interest in addressing its pathogenicity. While being primarily associated with hospital-acquired respiratory tract infections, this bacterial species is also relevant to ophthalmology, particularly to contact lens-related diseases. In the current study, the capacity of Stenotrophomonas phage vB_SmaM_Ps15 to infect ocular S. maltophilia strains was investigated to explore its future potential as a phage therapeutic. The phage proved to be lytic to a range of clinical isolates collected in Australia from eye swabs, contact lenses and contact lens cases that had previously shown to be resistant to several antibiotics and multipurpose contact lenses disinfectant solutions. Morphological analysis by transmission electron microscopy placed the phage into the Myoviridae family. Its genome size was 161,350 bp with a G + C content of 54.2%, containing 276 putative protein-encoding genes and 24 tRNAs. A detailed comparative genomic analysis positioned vB_SmaM_Ps15 as a new species of the Menderavirus genus, which currently contains six very similar globally distributed members. It was confirmed as a virulent phage, free of known lysogenic and pathogenicity determinants, which supports its potential use for the treatment of S. maltophilia eye infections.